2023
DOI: 10.1002/hsr2.1513
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of sexual distress in married reproductive‐age women: A cross‐sectional study from Iran

Zeinab Hamzehgardeshi,
Shadi Sabetghadam,
Mehdi Pourasghar
et al.

Abstract: Background and AimAlthough various surveys have been conducted for sexual problems, there is a lack of population‐based studies on sexual distress in Iran. Thus, we sought to determine the prevalence and predictive factors of sexual distress in this population.MethodsOverall, 1000 married women aged 16–49 years were enrolled in this study using the two‐stage cluster sampling method. To identify sexual distress, the female sexual distress scale‐revised (FSDS‐R) was completed. The predictive factors were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In preliminary research, the reliability of the Sexual Self-Efficacy Questionnaire was reported at 0.86 using Cronbach's alpha and 0.81 using the split-half method. Its validity was confirmed by Vaziri and Lotfi Kashani (2013) using content validation (Hamzehgardeshi et al, 2023;Hasani et al, 2021;Mosadegh et al, 2023;Shadanloo et al, 2023).…”
Section: Sexual Self-efficacymentioning
confidence: 86%
“…In preliminary research, the reliability of the Sexual Self-Efficacy Questionnaire was reported at 0.86 using Cronbach's alpha and 0.81 using the split-half method. Its validity was confirmed by Vaziri and Lotfi Kashani (2013) using content validation (Hamzehgardeshi et al, 2023;Hasani et al, 2021;Mosadegh et al, 2023;Shadanloo et al, 2023).…”
Section: Sexual Self-efficacymentioning
confidence: 86%
“…Women with erotophobia face numerous marital and sexual relationship problems, experiencing dissatisfaction, tension, and significant stress (Gregory, 2021). Sexual distress can cause severe anxiety about having sexual relations, potentially leading to avoidance of sexual activity (Hamzehgardeshi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%